2015
DOI: 10.1016/j.jtcme.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming of Ayurveda, Yoga, Naturopathy, Unani, Siddha, and Homeopathy with the health care delivery system in India

Abstract: India has a population of 1.21 billion people and there is a high degree of socio-cultural, linguistic, and demographic heterogeneity. There is a limited number of health care professionals, especially doctors, per head of population. The National Rural Health Mission has decided to mainstream the Ayurveda, Yoga, Naturopathy, Unani, Siddha, and Homeopathy (AYUSH) system of indigenous medicine to help meet the challenge of this shortage of health care professionals and to strengthen the delivery system of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 7 publications
0
39
0
1
Order By: Relevance
“…A number of countries include homeopathy in their publicly funded healthcare systems (UK, France, Italy, Germany, Switzerland, India, Pakistan, Brazil, and Mexico 53 ), yet our review identified estimates from only two of these countries e Switzerland (which has the highest estimate of treatment by a homeopath) and the UK (which had the highest estimate of all homeopathy use). No published English language surveys were identified in India, where homeopathy is a popular treatment modality 54 and considered part of mainstream medicine. We recommend that a further review is conducted which includes all languages.…”
Section: Discussionmentioning
confidence: 99%
“…A number of countries include homeopathy in their publicly funded healthcare systems (UK, France, Italy, Germany, Switzerland, India, Pakistan, Brazil, and Mexico 53 ), yet our review identified estimates from only two of these countries e Switzerland (which has the highest estimate of treatment by a homeopath) and the UK (which had the highest estimate of all homeopathy use). No published English language surveys were identified in India, where homeopathy is a popular treatment modality 54 and considered part of mainstream medicine. We recommend that a further review is conducted which includes all languages.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Indonesian government adopts Indian Ayurveda which includes the use of herbal medicines in healthcare services (Shrivastava, Shrivastava, & Ramasamy, 2015), and makes classification and enrichment of Jamu into Phytopharmacy, under the management of Department of Healthcare, as an important objective. A government regulation which includes Jamu as primary medication in public health care services and which gives more access to the testing of Jamu and its halal certification is much needed.…”
Section: Discussionmentioning
confidence: 99%
“…Other examinations of the functioning of co-located AYUSH and allopathic facilities have found little or no interaction, professional or social, among providers practising different systems of medicine at the same facility, no published protocol for cross-referral ( Shrivastava et al., 2015 , Chandra, 2011 , Priya, 2013 ), little or no cross-referral ( SEDEM, 2010 ), and no documentation of referral when it does occur ( Priya and Shweta, 2010 , Gopichandran and Kumar, 2012 , Priya, 2013 ).…”
Section: Discussionmentioning
confidence: 99%